Les métamorphoses pâlissantes dans les textes traduits: étude sur le jaune et le blond - Lécrivain, Claudine (Verbum – Analecta Neolatina, 2006)
The following analysis is a reflection on the translations of the colour yellow and the shades of blonde found in a body of French and Spanish literary texts in an attempt to delimit the situations in which literal translations of these terms occur. Our analysis shall examine situations where translators propose distinct types of distancing from these literal translations through an application of their own colour filter. These interpretative strategies eithermanifest an intensification of realism or, on the contrary, an almost spontaneous solution to codified reading practices.